أثر الفيضانات والسيول في العبادات: دراسة فقهية تحليلية - Mohd Izzuddin Mohd Noor (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The research addresses floods and torrents and how they affects the rules of worship ('Ibadah) such as (i.e cleansing of oneself (Taharah), prayer (Salah), fasting (Sawm), alms (Zakah) and pilgrimage (hajj). Inasmuch as the rules of Shari'ah relate to the acts of al-Mukallafin (who are legally competent to be responsible for religious duty), the effect of this kind of disaster reflects in the rules of victims' actions, in terms of its obligation or not. The research confirms that floods and torrents are among the reasons that allow for the rule of reduction, ease and exemption from some parts of obligation in Islam (Al- Rukhsah) because the situation is inconvenient and unbearable for the victims due to the hardship and necessity. So, considering their state of necessity, the rules of fiqh related to worship ('Ibadah) will be based on these maxims: 'Prevention and eradication of harm', 'Consideration of ease and reduction of burden'. The inductive methodology is applied in the research by generating and collecting data from the sources, as well as the analytical methodology, by analyzing the views of Islamic jurists on the topic. One of the main findings of the research is that floods and torrents have some adverse effects, such as bringing harm and damage to the people, putting the victims in a situation of unrest due to hardship and difficulty. In fact, the victims may be in the state of necessity, if some lives are lost. The victims of this disaster are permitted to use rules of 'Rukhsah' in their worship ('Ibadah), provided that hardship and necessity occur and so that the removing and eradicating hardship and difficulty are acquired. This verdict is based on Shari'ah evidences, such as the rule of analogy (al-Qiyas), blocking the means to hardship and necessity (Sadd al-dhara'i') and public/ unrestricted interest (al-Masalih Al-Mursalah).